2020
DOI: 10.14202/vetworld.2020.2411-2415
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leptospira in urine of apparently healthy dogs by quantitative polymerase chain reaction in Haryana, India

Abstract: Background and Aim: Leptospirosis is a zoonotic disease caused by bacteria of the genus Leptospira. The organism can spread through the urine of infected animals, which can get into water or soil and can survive there for weeks to months. The study was undertaken to detect the pathogenic Leptospira in healthy dogs' urinary shedding by real-time polymerase chain reaction (qPCR). Materials and Methods: Leptospirosis is a zoonotic disease caused by bacteria of the genus Leptospira. To detect the pathogenic Lepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Although several studies have demonstrated high specificity and sensitivity for real-time PCR and found it to be a rapid method for diagnosing acute leptospirosis (Stoddard et al, 2009), in the present study, specificity was high, but sensitivity low. Based on previous research, this can be explained by intermittent urinal Leptospira shedding, prior use of antibiotics before analysis, freezing of samples and the pH of urine, which can influence and reduce test sensitivity (Fraune et al, 2013;Rohilla et al, 2020;Schuller et al, 2015). Troìa et al (2018) also observed low diagnostic sensitivity for qPCR, with sensitivity and specificity of 13.5 and 92.0 %, respectively, similar to our findings.…”
Section: Resultssupporting
confidence: 87%
“…Although several studies have demonstrated high specificity and sensitivity for real-time PCR and found it to be a rapid method for diagnosing acute leptospirosis (Stoddard et al, 2009), in the present study, specificity was high, but sensitivity low. Based on previous research, this can be explained by intermittent urinal Leptospira shedding, prior use of antibiotics before analysis, freezing of samples and the pH of urine, which can influence and reduce test sensitivity (Fraune et al, 2013;Rohilla et al, 2020;Schuller et al, 2015). Troìa et al (2018) also observed low diagnostic sensitivity for qPCR, with sensitivity and specificity of 13.5 and 92.0 %, respectively, similar to our findings.…”
Section: Resultssupporting
confidence: 87%
“…The lateral flow immunochromatographic kit (LFK) is a simple, rapid test that can be carried out in the field. Now the LFK technology is widely used for the determination of bacterial pathogens in clinical samples of different diseases, such as S. aureus in clinical samples [ 8 ], S. aureus enterotoxin A in milk [ 9 ], Vibrio cholera [ 10 ], Vibrio harveyi [ 11 ], Yersinia pestis in humans [ 12 ], Leptospira in urine [ 13 ], Helicobacter pylori in stool [ 14 ], Streptococcus suis serotype 2 [ 15 ], Salmonella enterica subsp. Enterica serovar Typhimurium ( S. typhimurium ) [ 16 , 17 ], Candida albicans [ 18 ], and COVID-19 coronavirus [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Rats, canines, buffaloes, and cattle are the hosts for leptospirosis. 9 Humans or animals are infected accidentally by direct or indirect contact with leptospira infected animals or contaminated water or urine. 10,11 Infection is also possible by other methods, like handling clinically infected animal tissues, inhalation of droplets of urine, 12 and consuming contaminated food and water.…”
Section: Introductionmentioning
confidence: 99%